PENGARUH EFIKASI DIRI AI DAN PENGGUNAAN CHATGPT TERHADAP PERSEPSI AI: PERAN MEDIASI LITERASI AI - Citra Damayanti; Silky Roudhotus Sa’adah (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The rapid development of artificial intelligence (AI) has increased the use of ChatGPT in higher education, yet frequent use does not necessarily lead to positive perceptions of AI. This study examines the effects of AI self-efficacy and ChatGPT use on students’ perceptions of AI, with AI literacy as a mediating variable. A quantitative explanatory research design was employed. The population consisted of 479 Economic Education students at Universitas Sebelas Maret from the 2022–2025 cohorts. Using purposive sampling, 100 students who had used ChatGPT for academic purposes were selected as respondents. Data were collected through a four-point Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that AI self-efficacy has positive and significant effects on AI perception and AI literacy. ChatGPT use has a positive and significant effect on AI literacy but does not significantly affect AI perception. AI literacy positively and significantly affects AI perception. Furthermore, AI literacy partially mediates the effect of AI self-efficacy on AI perception but does not mediate the effect of ChatGPT use on AI perception. These findings underscore the importance of strengthening AI self-efficacy and AI literacy to support more informed perceptions of AI in learning. Keywords: AI self-efficacy, ChatGPT usage, AI perception, AI literacy.